2012
DOI: 10.1007/s10588-012-9149-3
|View full text |Cite
|
Sign up to set email alerts
|

Justification shift and uncertainty: why are low-probability near misses underrated against organizational routines?

Abstract: Knowledge of near misses is helpful in preventing accidents, but it does not always lead to changes in organizational routines or contribute to accident prevention. In this article, the authors argue that low-probability near misses reinforce beliefs of experts and professionals in existing routines, proposing a concept of justification shift. Justification shift is underestimation of risks of known near misses vis-à-vis overestimation of reliabilities of existing routines. Consequently, signals of "close call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Among the latter, some authors (e.g., Mungovan et al 2011;Shimazoe and Burton 2013) report convergence analysis to estimate the steady state. Instead, among the former, Siebers and Aickelin (2011) refer to Robinson (2004) to justify the choice of 20 runs per each configuration of parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Among the latter, some authors (e.g., Mungovan et al 2011;Shimazoe and Burton 2013) report convergence analysis to estimate the steady state. Instead, among the former, Siebers and Aickelin (2011) refer to Robinson (2004) to justify the choice of 20 runs per each configuration of parameters.…”
Section: Resultsmentioning
confidence: 99%
“…It was also acknowledged that, even with the best will, PSNMs are less likely to stimulate action and improvement as no harm occurs; PSNMs alone may not provide impetus for change. 41…”
Section: Discussionmentioning
confidence: 99%
“…Actions by aviators and flight crews are generally predictable based on Air Traffic Control directives, mandates from the FAA, directives from flight carriers, and actions of other aircraft operators. Research has shown that unless the high probabilities of risks are known, current routines are unlikely to change unless accidents or incidents have occurred (Shimazoe & Burton, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research has acknowledged that in the mind of the individual human decision maker, close calls are usually deemed as "successes" and the near misses reinforce the individual's current routine. When a "justification shift" occurs, it leads to an underestimation of the known risk (or close call) and an overestimation of the reliability of the routine (Shimazoe & Burton, 2013). To better communicate these risks, it is essential to first understand the differences that exist among the types of close call events.…”
Section: Introductionmentioning
confidence: 99%